The Biological Role of Nestin(+)-Cells in Physiological and Pathological Cardiovascular Remodeling - Calderone, Angelino (Frontiers in Cell and Developmental Biology, 2018)
The intermediate filament protein nestin was identified in diverse populations of cells implicated in cardiovascular remodelling. Cardiac resident neural progenitor/stem cells constitutively express nestin and following an ischemic insult migrate to the infarct region and participate in angiogenesis and neurogenesis. A modest number of normal adult ventricular fibroblasts express nestin and the intermediate filament protein is upregulated during the progression of reparative and reactive fibrosis. Nestin depletion attenuates cell cycle re-entry suggesting that increased expression of the intermediate filament protein in ventricular fibroblasts may represent an activated phenotype accelerating the biological impact during fibrosis. Nestin immunoreactivity is absent in normal adult rodent ventricular cardiomyocytes. Following ischemic damage, the intermediate filament protein is induced in a modest population of pre-existing adult ventricular cardiomyocytes bordering the peri-infarct/infarct region and nestin(+)-ventricular cardiomyocytes were identified in the infarcted human heart. The appearance of nestin(+)-ventricular cardiomyocytes post-myocardial infarction recapitulates an embryonic phenotype and depletion of the intermediate filament protein inhibits cell cycle re-entry. Recruitment of the serine/threonine kinase p38 MAPK secondary to an overt inflammatory response after an ischemic insult may represent a seminal event limiting the appearance of nestin(+)-ventricular cardiomyocytes and concomitantly suppressing cell cycle re-entry. Endothelial and vascular smooth muscle cells express nestin and upregulation of the intermediate filament protein may directly contribute to vascular remodelling. This review will highlight the biological role of nestin(+)-cells during physiological and pathological remodelling of the heart and vasculature and discuss the phenotypic advantage attributed to the intermediate filament protein.